2021
DOI: 10.1145/3463506
|View full text |Cite
|
Sign up to set email alerts
|

Contrastive Predictive Coding for Human Activity Recognition

Abstract: Feature extraction is crucial for human activity recognition (HAR) using body-worn movement sensors. Recently, learned representations have been used successfully, offering promising alternatives to manually engineered features. Our work focuses on effective use of small amounts of labeled data and the opportunistic exploitation of unlabeled data that are straightforward to collect in mobile and ubiquitous computing scenarios. We hypothesize and demonstrate that explicitly considering the temporality of sensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 75 publications
(79 reference statements)
0
77
0
Order By: Relevance
“…It has demonstrated strong recognition when data from both accelerometer and gyroscope are available. Contrastive Predictive Coding (CPC) [31]: adopted and applied the contrastive predictive coding framework to wearable data, and makes use of long term temporal properties for effective representation learning by predicting multiple future timesteps. It performs successfully for activity recognition and semi-supervised learning, especially when multiple sensors are available.…”
Section: Self-supervised Har Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has demonstrated strong recognition when data from both accelerometer and gyroscope are available. Contrastive Predictive Coding (CPC) [31]: adopted and applied the contrastive predictive coding framework to wearable data, and makes use of long term temporal properties for effective representation learning by predicting multiple future timesteps. It performs successfully for activity recognition and semi-supervised learning, especially when multiple sensors are available.…”
Section: Self-supervised Har Methodsmentioning
confidence: 99%
“…The Contrastive Predictive Coding (CPC) framework was adopted and applied to human activity recognition in [31]. Windows of accelerometer and gyroscope data from mobile phones are encoded with a 1D convolutional encoder.…”
Section: Self-supervised Learning In Human Activity Recognitionmentioning
confidence: 99%
“…For a federated learning framework involving multiple sensors, such as WiFi, IMU, electroencephalogram, and blood volume pulse, Saeed et al [43] applied contrastive learning with wavelet transformations. Combining contrastive learning with predictive coding, Haresamudram et al [44] showed that the performance of downstream classification tasks could be significantly improved.…”
Section: Transfer Learning and Self-supervised Learningmentioning
confidence: 99%
“…Recently, semi-supervised and especially self-supervised learning methods [101][102][103] have become popular in many machine learning application domains including human activity recognition using wearables [13,43,44]. Here the idea is to enhance small amounts of labeled data through specific modification, formalized through so-called pretext learning tasks, such that, through solving the auxiliary task, a meta-learning procedure is forced to learn higher-level concepts that eventually lead to improved activity recognition performance.…”
Section: Virtual Imu Data As Basis For Alternatives To Supervised Learningmentioning
confidence: 99%
“…Its key idea is to conduct a discriminative learning approach to learn encoded feature representations, in which similar sample pairs remain close together, whereas different sample pairs remain widely apart. It has been successfully verified in many computer vision tasks such as image classification [ 17 ] and human activity recognition [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%